THE ESSENCE OF QUALITY EDUCATIONAL SERVICES IN MADRASA IBTIDAIYAH - Subki, Imam; Baharun, Hasan; Hamid Wahid, Abdul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to determine the essence of the quality of educational services in Islamic elementary schools. The method and type of data collection in this research is a research library by collecting books, journals and the results of previous studies that support the research theme. The concept of quality education refers to policies, teaching and learning processes, curriculum, infrastructure and educational staff. This quality must refer to the achievement of progress based on planned changes. There are two strategies for quality educators, namely academy-oriented education to provide a minimal basis in the course of education required by the demands of the times and improve the quality of education that is oriented towards life skills.